(untitled) (Research, Society and Development, 2025)
Fabry Disease (FD) is a rare X-linked genetic disorder characterized by a deficiency of the enzyme alpha-galactosidase A, resulting in the accumulation of glycosphingolipids and multisystemic involvement. This study, based on an integrative literature review, aims to investigate the relationship between DM and auditory alterations such as tinnitus, vertigo, and sudden or progressive hearing loss. Data show that patients with FD have a significantly increased risk of cochleovestibular disorders due to underlying vascular pathology. Early audiological evaluation is essential, particularly in patients with renal, cardiac, or neurological complications. Enzyme replacement therapy (ERT) has proven effective in stabilizing disease progression and improving quality of life, with early initiation being recommended. The study highlights the importance of early diagnosis and systematic otolaryngological screening in individuals with FD.